EFISIENSI UNIT PENGUMPULAN ZAKAT (UPZ) DALAM MENGELOLA ZAKAT UNTUK MEMPERKUAT PEREKONOMIAN RAKYAT - BANGO, FAISAL S; DJAFAR, LUCYANE; MOZIN, NOPIANA; BANGO, FIKRAN S (Ganec Swara, 2025)
This research aims to discuss the implementation of zakat fund management, a study of the zakat collection unit of Tenggela village. In the study, a qualitative method with a descriptive approach was used. Data was obtained through observation, documentation, and direct interviews with informants to strengthen the data obtained by the researcher. The results of this study show that first, effective and transparent communication is essential, with zakat collection carried out through methods such as mosque announcements, village officials’ administrative management, and tiered announcements from the Government. Human Resources (HR) plays a crucial role in the success of the Zakat Collection Unit (UPZ), and improving the quality and competence of human resources is very necessary, especially when involving the younger generation. Suitable management structures, experience, transparency, and coordination between related parties must be strengthened. Meanwhile, the level of public awareness in paying for Zakat is influenced by internal factors such as religiosity and psychological motivation, as well as external factors such as government regulations and attributes of Zakat institutions. Internal factors play a significant role in shaping public awareness and compliance with zakat obligations, while external factors can strengthen this awareness when socialized and implemented correctly. Religious education, regulatory socialization, transparency, and professionalism of zakat institutions are critical in increasing public trust and participation.